PENGGUNAAN MEDIA VIDEO DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN PAI DI SMPN 1 PADANG GELUGUR - Roy Poso; Edi Saputra; Alfurqan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the use of instructional video media in improving Islamic Religious Education (PAI) learning outcomes for eighth-grade students of class VIII-3 at SMPN 1 Padang Gelugur. This study uses a qualitative approach carried out through three stages, namely the planning stage, implementation stage, and reporting of research results. Data collection techniques were conducted through observation, interviews, and documentation. In the planning stage, the teacher prepares the Lesson Plan (RPP), selects video media appropriate to the material on believing in the books of Allah, and adjusts the video duration so that learning runs effectively and efficiently. The implementation stage is carried out by presenting the instructional video, followed by dividing students into discussion groups to discuss the Zabur, Taurat, Injil, and Al-Qur’an. The teacher then provides additional explanations, evaluations, and assignments to the students. The results of observations and interviews indicate that the use of learning video media can increase students' interest, activeness, and understanding in Islamic Religious Education (PAI) learning. This has an impact on improving students' learning outcomes, as shown by an average score of 80, which is above the Minimum Competency Criteria (KKM), compared to before the use of learning video media. Therefore, it can be concluded that the use of learning video media is effective in improving learning outcomes in Islamic Religious Education and creating a more engaging and meaningful learning process. Keywords: learning video media, learning outcomes, Islamic Religious Education